2014
DOI: 10.1016/j.immuni.2014.09.009
|View full text |Cite
|
Sign up to set email alerts
|

C-Type Lectin-like Receptor LOX-1 Promotes Dendritic Cell-Mediated Class-Switched B Cell Responses

Abstract: SUMMARY Lectin-like oxidized low-density lipoprotein receptor-1 (LOX-1) is a pattern recognition receptor for a variety of endogenous and exogenous ligands. However, LOX-1 function in the host immune response is not fully understood. Here, we report that LOX-1 expressed on dendritic cells (DCs) and B cells promotes humoral responses. On B cells LOX-1 signaling upregulated CCR7, promoting cellular migration towards lymphoid tissues. LOX-1 signaling on DCs licensed the cells to promote B cell differentiation int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 54 publications
1
64
0
Order By: Relevance
“…A recombinant fusion protein of humanized aCD40 antibody (12E12) and HPV16.E6/7 (aCD40-HPV16.E6/7) was generated as previously described (31,33,34). The fusion protein aCD40-HPV16.E6/7 carries HPV16.E6 1-120 /E7 1-60 appended to the heavy chain C-terminus ( Fig.…”
Section: Acd40-hpv16e6/7 Recombinant Fusion Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…A recombinant fusion protein of humanized aCD40 antibody (12E12) and HPV16.E6/7 (aCD40-HPV16.E6/7) was generated as previously described (31,33,34). The fusion protein aCD40-HPV16.E6/7 carries HPV16.E6 1-120 /E7 1-60 appended to the heavy chain C-terminus ( Fig.…”
Section: Acd40-hpv16e6/7 Recombinant Fusion Proteinmentioning
confidence: 99%
“…1B, right). All proteins were expressed by CHO-S cells and purified by protein A affinity chromatography (30,31,33,34).…”
Section: Acd40-hpv16e6/7 Recombinant Fusion Proteinmentioning
confidence: 99%
“…We also found that the sLOX-1 level correlated with the titer of RF or ACPAs; the RF titer in particular correlated strongly with the sLOX-1 level. Because B cells reportedly express LOX-1 and may be programmed to promote class-switched antibody responses [27], LOX-1 expression might be involved in the production of autoantibodies in patients with RA or vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Env gp140 sequence derived from the codon-optimized HIV-1 96ZM651 synthetic construct (NIH AIDS reagent program, GenBank accession number AY181197.1 residues 94 to 2064) was inserted at the IgG4 heavy-chain C-terminal codon distal to a flexV1 flexible linker spacer (9) and proximal to 6 His codons. Anti-LOX-1.Env gp140 (2) was derived from the parental anti-human LOX-1 15C4 recombinant human IgG4 MAb (3,22) (GenBank accession numbers KM246787 and KM246788) via humanization of the mouse variable regions (Antitope, Ltd.). This was fused to Env gp140 sequence as described above.…”
Section: Methodsmentioning
confidence: 99%
“…In a prior study (2), we investigated the efficacy in nonhuman primates (NHPs) of a humanized anti-human LOX-1 antibody fused to Env gp140 for eliciting cellular and humoral immunity against gp140 in both prime and boost settings. Based on in vitro and in vivo studies of targeting antigens to LOX-1 on antigen-presenting cells (APCs), targeting Env to LOX-1 was predicted to favor humoral immunity (3). However, it is not yet clear which DC surface receptors are the best targets for particular protective immune responses (4)(5)(6).…”
mentioning
confidence: 99%